PENGARUH GENDER, RELIGIUSITAS DAN LOVE OF MONEY TERHADAP PERSEPSI PENGHINDARAN PAJAK (Studi Kasus Pada Wajib Pajak Orang Pribadi Yang Terdaftar di KPP Pratama Kota Tegal) - Rania, Latifa; Setyanto, Eko (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
Gender, religiosity and love of money are factors that allow someone to avoid taxes. This research aims to determine the influence of gender, religiosity |and love of money |attitudes on perceptions of t|ax |avoid|ance |at the Teg|al City Pr|at|am|a T|ax Service Office. This rese|arch is qu|antit|ative rese|arch using prim|ary d|at|a. The s|ampling technique in this rese|arch w|as c|arried out by purposive s|ampling. The results of this rese|arch show: 1) Gender, religiosity |and love of money h|ave |a signific|ant effect on perceptions of t|ax |avoid|ance, 2) Hypothesis test results show th|at there is no signific|ant difference reg|arding perceptions of t|ax |avoid|ance between m|ale t|axp|ayers |and fem|ale t|axp|ayers. In this case, male taxpayers do not have a lower perception than female taxpayers. Likewise, on the other hand, female taxpayers do not have lower perceptions than male taxpayers. 3) Hypothesis test results show that religiosity has a significant positive effect on tax avoidance. 4) Hypothesis test results show that the love of money attitude has a significant negative effect. towards the ethics of tax avoidance.